Biocompatible thin films obtained from Heparim-methane plasma process - Mota, R. P.; Perrenoud, I. A.; Honda, R. Y.; Algatti, M. A.; Kayama, M. E.; Kostov, K. G.; Sadahito China, T.; Cruz, N. C. (International Conference on Plasma Surface Engineering, 2013)
Heparin is an appropriate molecule to suppress the thrombus formation in the initial stages of blood contact with an artificial material. Therefore the covering of a synthetic material with heparin-like molecules is a great importance issue in biomaterial science and engineering. In order to reach this goal this paper deals with the plasma deposition of thin heparin-like films on microscope slides from RF-excited heparin/methane low pressure plasmas. Plasma were excited by a RF-power supply operating on 13.56 MHz at a fixed power of 50 W. Heparin was diluted in ethanol and fed into the plasma chamber in mixtures of 50% of CH4 (in pressure) at 10 Pa. Films molecular structure was characterized by Fourier transform infrared spectroscopy (FTIR here in). Molecular spectra presented absorption bands due C-H, O-H and C-O stretching and bending modes. Films surface wettability was investigated by contact angle measurements. The experimental results show values varying from 650 to 200. Surfaces optical microscopy showed the occurrence of heparin islands distributed almost uniformly over the _lm. The bloods coagulation time placed in contact with glass substrate covered by plasma deposited heparin/methane films was measured by thrombosis time and activated thromboplastin.